The Impact of the 7 Habits of Great Indonesian Children Program on the Discipline of Second Grade Students at SDN 2 Sibalung - Sunarsih Sunarsih; Sriyanto Sriyanto (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to examine the impact of the "7 Habits of Great Indonesian Children" program on the discipline levels of second-grade students at SDN 2 Sibalung. This initiative, launched by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek), seeks to instill positive character values through daily habits such as waking up early, religious observance, maintaining health, consuming nutritious food, fostering a love for learning, socializing, and ensuring quality sleep. The research employs a literature review method to analyze relevant sources. The findings indicate that the program positively influences students' discipline levels. Consistent application of these values has been shown to enhance students' adherence to school rules and their sense of responsibility. However, the implementation faces challenges, including limited supporting facilities, varying family backgrounds, and insufficient community support. Therefore, collaboration among schools, families, and communities is essential for the sustainable success of the program.